Clinical outcome in 22 patients with rheumatoid arthritis treated with B lymphocyte depletion. Issue 10 (1st October 2002) - Leandro, M J; Edwards, J C W; Cambridge, G
Abstract : Objectives: To obtain evidence for dose response and to extend evidence of safety and efficacy for B lymphocyte depletion in rheumatoid arthritis. Methods: Twenty two patients with rheumatoid arthritis received a total of 29 treatments with five different combinations of rituximab (RTX), cyclophosphamide (CP), and/or high dose prednisolone (PR) on an open basis as follows; cohort I: RTX 1400 mg/m 2, CP 750×2+PR; cohort II: RTX 300–700 mg/m 2, −CP±PR); cohort III: RTX 600–700 mg/m 2, CP 750×2+PR; cohort IV: RTX 1200 mg/m 2, CP 750×2−PR; cohort V: RTX 500 mg/m 2, CP 750×2+PR. American College of Rheumatology (ACR) criteria of improvement at six months were chosen as the primary outcome measure. Disease activity scores and total duration of improvement and of B cytopenia were also recorded. Results: No major adverse events attributable to treatment were seen. ACR grades of improvement at six months were as follows: cohort I: ACR70×3, ACR50×2; cohort II: ACR20×1, ACR0×3; cohort III: ACR70×6, ACR50×2, ACR20×2; cohort IV: ACR70×2, ACR50×2, ACR20×1, ACR0×1; cohort V: ACR0×4. Conclusions: B lymphocyte depletion in rheumatoid arthritis has so far proved to be safe and associated with major improvement with protocols including RTX 600 mg/m 2 or more and CP, but not with more limited protocols. These observations provide an initial basis for the design of formal trials of B cell depletion and other B cell directed treatments, including a phase II controlled trial now in progress.